Pemberdayaan Masyarakat Nagori Karang Sari melalui Penguatan Literasi Digital dan Ekonomi Kreatif - Syahfitri, Rizki Ananda; Simanjuntak, Nurhasanah; Rangkuti, Muhammad Habibi; Hanif, M Rofi; Aslami, Nuri (Jurnal IPTEK Bagi Masyarakat, 2025)
The Karang Sari community faces limitations in digital literacy and access to local product marketing, hindering economic independence and strengthening social and spiritual character. This activity aims to improve digital capacity, creative entrepreneurship, and religious awareness of residents through the Community Service Program (KKN) with a multidimensional approach encompassing social education, digital literacy, the creative economy, and religious activities. The method used was field-based descriptive qualitative research, involving training, mentoring, participatory observation, and documentation of primary and secondary data. The results showed that 30 MSMEs successfully created digital business accounts, improved creative product management skills, and strengthened understanding of worship and religious moderation through the Fardu Kifayah Training, Dawn Lectures, and the Pious Children Festival. The impact of this program is reflected in the increased social, economic, and spiritual capacity of the community, strengthening the independence and well-being of the local community, while simultaneously shaping children's religious character and better social awareness. Further recommendations include ongoing mentoring for the development of a more massive creative economy and digital literacy to ensure the sustainability of the positive impact.